"Only YOU Can Prevent This Nightmare, America": Nancy Pelosi As the Monstrous-Feminine in Donald Trump's YouTube Attacks. Issue 3 (3rd July 2022) - Phipps, E. Brooke; Montgomery, Fielding
Abstract: The construction of Nancy Pelosi as the monstrous-feminine reveals itself in the highly misogynistic attack advertisements of Donald Trump's 2020 presidential reelection campaign. In our analysis of five YouTube attack ads, we demonstrate how short-form digital advertisements use the conventions of digital platforms to heighten the elements of horror used to construct the monstrous-feminine. Drawing from horror genre logics and editing conventions, the Trump campaign produces a narrative strategy that preys on conservative fears regarding women, race, and breaches in a gendered social contract. Targeting one of the most powerful women in American politics, Trump's digital ads deploy a variety of editing strategies combined with common horror tropes to push audiences toward violent conclusions of how to "defeat" the monstrous-feminine, Pelosi.